2012
DOI: 10.1111/jnc.12044
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the branched chain aminotransferase proteins in the human brain and their role in glutamate regulation

Abstract: The branched chain aminotransferase enzymes (BCAT) serve as nitrogen donors for the production of 30% of de novo glutamate synthesis in rat brain. Despite the importance of this major metabolite and excitatory neurotransmitter, the distribution of BCAT proteins in the human brain (hBCAT) remains unreported. We have studied this and report, for the first time, that the mitochondrial isoform, hBCATm is largely confined to vascular endothelial cells, whereas the cytosolic hBCATc is restricted to neurons. The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 61 publications
5
75
0
Order By: Relevance
“…All IDH-WT tumours examined have increased expression of the BCAA metabolic proteins relative to normal brain tissue (Hull et al, 2012). Western blot analysis has demonstrated that in IDH-WT tumours there was a significant increase in the expression of hBCATm (p=0.036) and hBCATc (p=0.007) relative to IDH mutation glioblastomas ( Figure 1A and B).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…All IDH-WT tumours examined have increased expression of the BCAA metabolic proteins relative to normal brain tissue (Hull et al, 2012). Western blot analysis has demonstrated that in IDH-WT tumours there was a significant increase in the expression of hBCATm (p=0.036) and hBCATc (p=0.007) relative to IDH mutation glioblastomas ( Figure 1A and B).…”
Section: Resultsmentioning
confidence: 95%
“…Under normal physiological conditions, the hBCAT isoforms show both tissue and cell specific expression (Hull et al, 2012), which makes their co-expression in gliomas most unusual, highlighting new regulatory mechanisms for the BCAT genes under pathogenic conditions. Here, we report that the mitochondrial isoform, hBCATm, was also significantly (p=0.036) increased in IDH-WT tumours and more importantly is a negative predictor of patient survival in IDH-WT glioblastomas (p=0.003) and also in grade IV tumours alone (p=0.043).…”
Section: P a G Ementioning
confidence: 99%
“…Like the rat/mouse, BCATc is primarily found in neurons that are GABAergic or glutamatergic with more immunopositive GABAergic neurons [22]. As in rodents, neurons that were neither glutamatergic nor GABAergic were also labeled (serotonergic, dopaminergic) with some neuroendocrine cells also showing BCATc immunolabeling.…”
Section: Shuttling Of Bcaa Metabolites and Their Role In Brain Metabomentioning
confidence: 97%
“…These proteins have a mitochondrial (m) and cytosolic (c) isoform with tissue-specific locations, with hBCATm, the most ubiquitous isoform, thought to be responsible for the majority of transamination outside the central nervous system with the highest levels of hBCATm recorded in the pancreas, kidney, stomach, and brain (70). hBCATc, is largely associated with neuronal cells and is predominantly found in the soma and proximal dendrites of glutamatergic and GABAergic neuronal cells, supporting its role in contributing to both the storage and metabolic pools of the neurotransmitter glutamate and as the precursor for GABA production in GABAergic neurons (71)(72)(73). Although hBCATm is ubiquitously expressed throughout the body, there is extensive immuno-positive staining for hBCATm specific to brain vasculature, indicating a new role for hBCATm in brain glutamate regulation (71,74).…”
Section: Metabolic Redox Chaperones: the Hbcat Proteins Transaminatiomentioning
confidence: 99%
“…hBCATc, is largely associated with neuronal cells and is predominantly found in the soma and proximal dendrites of glutamatergic and GABAergic neuronal cells, supporting its role in contributing to both the storage and metabolic pools of the neurotransmitter glutamate and as the precursor for GABA production in GABAergic neurons (71)(72)(73). Although hBCATm is ubiquitously expressed throughout the body, there is extensive immuno-positive staining for hBCATm specific to brain vasculature, indicating a new role for hBCATm in brain glutamate regulation (71,74). BCAT catalyse the transfer of the α-amino group from the hydrophobic branched-chain amino acids (BCAAs) leucine, isoleucine, and valine, to α-ketoglutarate releasing their respective keto acids, ketoisocaproate, keto methyl valerate, and ketoisovaline and glutamate, regenerating the enzyme (75,76).…”
Section: Metabolic Redox Chaperones: the Hbcat Proteins Transaminatiomentioning
confidence: 99%